Analysis of Threat Detection, Prevention Strategies, and Cyber Risk Management for Computer Network Security in Government Information Systems in Indonesia - Rifky Lana Rahardian; Hanifah Nurul Muthmainah; Moh. Erkamim; Loso Judijanto (West Science Information System and Technology, 2023)
This research investigates the landscape of threat detection, prevention strategies, and cyber risk management within Government Information Systems in Indonesia. A quantitative approach, employing Structural Equation Modeling - Partial Least Squares (SEM-PLS), was utilized to analyze data collected from 150 participants across diverse government institutions. The study assessed perceived cyber threats, the effectiveness of threat detection mechanisms, prevention strategy implementation, and cyber risk management practices. Findings revealed significant regional variations in threat perception and underscored the importance of both technological and human-centric approaches. The Structural Equation Model demonstrated satisfactory fit, with notable path coefficients indicating strong relationships among latent variables. The study contributes valuable insights to cybersecurity practices in the Indonesian government sector, informing policymakers and practitioners on strategies to enhance network security resilience.